Peran Istri Pembudidaya Rumput Laut (Eucheuma cottonii) dalam Meningkatkan Pendapatan Keluarga di Desa Teluk Singkama Kecamatan Sangatta Selatan Kabupaten Kutai Timur - Nurjanah; Nurul Ovia Oktawati; Heru Susilo (2339-1324, 2022)
The study's objectives were to know the working time and contribution of seaweed farmings' wives to increase the family income. The study was conducted in Teluk Singkama Village with 11 seaweed farmings' wives as respondents using by census method. The results showed that respondents' average working time for domestic activities was 3 hours 11 minutes daily. The mean working time of respondents for productive activities was 8 hours 19 minutes daily. Moreover, daily personal and leisure activities were 8 hours 17 minutes and 4 hours 11 minutes, respectively. The contribution of seaweed farmings' wives was low with the percentage criteria of 0-25%. Keywords : Seaweed farming, Eucheuma cottonii, Family income